The HIV epidemic in Sub-Saharan Africa is aging: evidence from the demographic and health surveys in Sub-Saharan Africa - Vollmer, Sebastian; Bärnighausen, Till (Aids and behavior, 2017)
We use the individual-level data from all available Demographic and Health Surveys (DHS) from 27 sub-Saharan African countries conducted between 2003 and 2012 (40 population-based and nationally representative surveys in total) to calculate HIV testing consent rates and HIV prevalence for each country separately, as well as for the pooled sample. The pooled sample comprised of 427,130 individuals. In most countries HIV prevalence in adults aged 45 years and above is higher than in the total population. We further show that over the past decade HIV prevalence has increased in older age groups, while it has decreased in younger ones. While the age patterns of HIV consent rates vary across the 27 countries included in our sample, analysis of the pooled sample across all countries reveals a u-shaped relationship with lowest consent rates around age 35 years and higher consent rates among younger and older people. We argue that future DHS and other population-based HIV surveys should offer HIV testing to all adults without age limits.